Kant in Schiller: moralni zakon, nagnjenja in vrlina – I. del - Kante, Božidar (Analiza: časopis za kritično misel, 2023)
Kant and Schiller: Moral Law, Inclinations, and Virtue - Part I.Schiller – in contrast to Kant – relocated or situated beauty in the realm of practical reason in Kallias. This means that the principle of beauty is not constitutive but rather regulative, which, in other words, implies that everyone should perceive beauty in the object. According to Schiller, beauty is nothing but freedom in appearance. The question is which appearances deserve to be interpreted in this way? Schiller is convinced that we attribute freedom to those objects that are self-determining, those that act solely from themselves. His »objective« principle should be interpreted only in terms of »subjective universality«. In this sense, Schiller does not advance beyond Kant, who also supports »subjective universality«. The article compares the viewpoint of Schiller on one side and Kant on the other and concludes that, based on the analyzed topic, here Schiller was a step ahead of Kant, and it took Kant a few years to arrive at an almost identical position.
Keywords: Schiller; Kant; beauty; moral law; virtue